Capsid Gene Divergence of Black Queen Cell Virus Isolates in Thailand and Japan Honey Bee Species - Wannapha Mookhploy (2018)
© 2015 The Authors. Black queen cell virus (BQCV) has been found in honey bees worldwide. By using the reverse transcription polymerase chain reaction (RT-PCR) technique, BQCV was detected in a non-native species, Apis mellifera L., collected in both Thailand and Japan, and three other honey bee species (Apis cerana indica F., Apis dorsata F., and Apis florae F.) native to Thailand and Apis cerana japonica F. native to Japan. Based on the capsid coding region, the phylogenetic analysis showed that the BQCV strains found in A. cerana indica and A. cerana japonica were similar within the group and closer to BQCV in Asia. It is interesting to note that the genetic variation of the BQCV isolates was more associated with geographic origin than the host bee species from which the isolates were obtained.